IMPLEMENTATION OF STRING SIMILARITY ALGORITHM IN PUBLIC COMPLAINT APPLICATIONS TO MINIMIZE SIMILAR COMPLAINTS - Dedi Gunawan; Ahimsa Prana Aditya (LPPM Nusa Mandiri, 2023)
Presently, the complaining service in Kartasura local government relies on manual recording where people must come to the government office, write their complaints and submit them to the office staff. This situation causes inefficiency since people have to travel from their places to the local government office. Moreover, the manual recording makes the complaints cannot be managed properly since the same complaints can be submitted more than one time. Additionally, it also causes some confusion to the government staff since they need to carefully check whether it has been submitted previously and approve the complaints accordingly. To solve the issue, a web-based application complaint system is developed to reduce the number of the same complaints from the citizen as well as to help staff manage the complaints data. The Jaro-Winkler String Similarity algorithm is adopted to check the similarity of newly submitted complaints with existing complaints data. The algorithm detects similarities of newly submitted complaints by determining the level of string equality to the existing complaints. Experimental results using one month period of complaints data in December 2022 show that the application is able to detect the similarity between the newly submitted complaints to the existing complaints. As the value of similarity threshold is higher, the number of rejected complaints also increases. Meanwhile, the test results of the system using the System Usability Scale Score obtained an average value of 76.5, which means the system is included in the Acceptable category and can be used for daily activity.